Study on properties of 3D-printed GelMA hydrogel scaffolds with different nHA contents. (September 2022) - Wang, Yaocheng; Lin, Chengxiong
Biological 3D printing is a reliable technology for 3D printing bone repair scaffolds with simple operation, high efficiency, and relatively low cost. Gelatin methacryloyl (GelMA) hydrogels have attracted much attention due to their good biocompatibility, but the poor mechanical properties limit their application in bone reconstruction engineering. In this study, nano-hydroxyapatite (nHA) particles were added to GelMA hydrogels, and the performances of composite hydrogel scaffolds with different nHA contents were investigated in terms of rheological properties, light transmission properties, surface morphology, mechanical properties, and biocompatibility. The experimental results showed that the incorporation of nHA particles could effectively improve the printability and mechanical properties of the scaffolds, the scaffold fibers had better resistance to deformation, improved degradation rate, and biological experiments confirmed that nHA particles had no significant cytotoxicity. However, the addition of HA particles also reduced the light transmission properties of the slurry, and when its content exceeds a certain value, the hydrogel scaffolds show incomplete curing and eventually affect their test performance. The results can offer guidance and reference for the selection of ink and function for 3D printing bone repair scaffold.